Response of the temporomandibular joint tissue of rats to rheumatoid arthritis induction methods - Ding-Han Wang; Mu-Chen Yang; Wun-Eng Hsu; Ming-Lun Hsu; Ling-Ming Yu (Elsevier, 2017)
Background/purpose: The pathogenesis of rheumatoid arthritis (RA)-related temporomandibular joint (TMJ) disorder remains unclear. Studies have reported the change of the TMJ after complete Freund's adjuvant (CFA) injection, which is consistent with osteoarthritis. However, few studies have reported that the tissue response of the TMJ in collagen-induced arthritis (CIA) can mimic RA. The present study was aimed to investigate the TMJ response in rat models by CFA-induced arthritis and CIA to verify the proper RA-related TMJ arthritis rat model. Materials and methods: In total, 24 rats were randomly divided into four groups: (1) control group; (2) type I collagen injection group; (3) CFA-induced arthritis group; and (4) CIA group. Drugs were injected on Day 0, and the rats were sacrificed on Days 7 and 35. Next, TMJ tissue was collected for hematoxylin and eosin staining, and inflammatory gene (IL-1β and MMP3) expression was investigated. Results: Compared with the control group, the type I collagen injection group confirmed the negative inflammatory response through hematoxylin and eosin staining and IL-1βand MMP3 expression. Although CFA-induced arthritis and CIA groups showed inflammatory response (P<0.05) compared with the control group, histological changes were different. The 7-day CFA-induced arthritis group showed adaptive changes and partly recovered after 35 days of induction. In contrast, 7- and 35-day CIA groups underwent a degenerative process. Conclusion: Considering the study limitations, the CIA method is a proper method to study the mechanism of RA-related TMJ arthritis.